Role of adiponektin and leptin in the development of metabolic syndrome and related obesity and type II diabetes mellitus - E. A. Shevchenko; T. E. Potemina; A. N. Uspensky (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Every year the number of people suffering from metabolic syndrome is growing steadily. Associated obesity, type II diabetes mellitus is currently among the most common diseases. Cytokines produced by adipose tissue play the role of regulators in metabolism, with obesity, a change in their secretion occurs and the balance is disturbed, which leads to the development of insulin resistance, and later – metabolic syndrome and type II diabetes mellitus. The study of the mechanisms of the influence of adipokines, in particular adiponectin and leptin, on energy, carbohydrate and lipid metabolism are of greatest interest due to their key role in the development of metabolic disorders.